Metodologia para quantificação de leucóciotos totais em peixe Oreochromis Niloticus - Ishikawa, Nilton Massuo [UNESP]; Ranzani-Paiva, M. J. T.; Lombardi, J. V. (My University, 2008)
Haematological investigation is an important part of disease diagnosis. The techniques used for mammals are generally applicable for fishes with slight modification. The presence of nucleated erythrocytes and thrombocytes in fish may cause some confusion in the identification of blood cells, mainly in total leukocytes count. This work evaluated two different methods (direct and indirect) of leukocytes counting. Specimens of tilapia were divided randomly into four groups of 48 fish each. Each group was further randomized into three replicate experiments of 16 fish per replicate in 40 L aquarium and maintained for 10 days. Counting of leukocytes in peripheral blood was determined in six fishes per group at the times: 0, 3, 7 and 10 days. The direct method in Neubauer chamber showed a large dispersion of data in regard to the average, the opposite was observed in indirect method determined in blood smears that showed more homogeneity among groups. Due to this factor the indirect method can be considered more accurate than the direct method for counting leukocytes in fishes.
Total leukocyte counts methods in fish, Oreochromis niloticus
Keywords: Blood; Fish; Leukocytes; Oreochromis niloticus; Mammalia; Pisces; Tilapia